Candida albicans: The Ability to Invade Epithelial Cells and Survive under Oxidative Stress Is Unlinked to Hyphal Length - Maza, Paloma K.; Bonfim-Melo, Alexis; Padovan, Ana C. B.; Mortara, Renato A.; Orikaza, Cristina M.; Ramos, Lilian M. Damas; Moura, Tauany R.; Soriani, Frederico M.; Almeida, Ricardo S.; Suzuki, Erika; Bahia, Diana (Frontiers in Microbiology, 2017)
In its hyphal form, Candida albicans invades epithelial and endothelial cells by two distinct mechanisms: active penetration and induced endocytosis. The latter is dependent on a reorganization of the host cytoskeleton (actin/cortactin recruitment), whilst active penetration does not rely on the host's cellular machinery. The first obstacle for the fungus to reach deep tissues is the epithelial barrier and this interaction is crucial for commensal growth, fungal pathogenicity and host defense. This study aimed to characterize in vitro epithelial HeLa cell invasion by four different isolates of C. albicans with distinct clinical backgrounds, including a C. albicans SC5314 reference strain. All isolates invaded HeLa cells, recruited actin and cortactin, and induced the phosphorylation of both Src-family kinases (SFK) and cortactin. Curiously, L3881 isolated from blood culture of a patient exhibited the highest resistance to oxidative stress, although this isolate showed reduced hyphal length and displayed the lowest cell damage and invasion rates. Collectively, these data suggest that the ability of C. albicans to invade HeLa cells, and to reach and adapt to the host's blood, including resistance to oxidative stress, may be independent of hyphal length.